KEKUATAN PASAR DALAM PERDAGANGAN BERAS DI KOTA TASIKMALAYA - Rudhiana Salam; Januar Arifin Ruslan; Rizki Risanto Bahar; Leny Yuliyani; Dira Asri Pramita; Sawitania Christiany Dwi Utami Boru Situmorang; Dedi Darusman (Jurnal Agristan, 2023)
Inflation occurs in food prices, especially rice, which is related to price formation at final consumer level. Market institution adjust their behavior in the face of the market structure. This study aims to analyze existence of market power in the formation of rice prices at the end -consumer level. The data used is weekly price of rice according to quality during the 2019 - 2022 period in Tasikmalaya City. Data analysis was performed using error correction model. Results of the analysis show that there is market power in four of the six qualities of rice traded in Tasikmalaya City. Price setting at various price qualities traded at the retail level is also necessary as an effort to prevent significant price changes such as price regulation at the producer level. Keywords: rice, behavior, market power